Double Aortic Arch with Coarctation of Aorta in an Adolescent: Unraveling the Vascular Ring - Rajbanshi, Bijoy G.; Acharya, Anil; Neupane, Prabesh; Gautam, Milan; Sharma, Apurb; Kayastha, Bhuwan; Ghimire, Ram K.; Sharma, Ranjit; Joshi, Lava N. (AORTA, 2020)
We report the case of a 12-year-old girl with balanced double aortic arch with coarctation of the aorta presenting with symptoms of respiratory and swallowing difficulty. On investigation, the patient had a double aortic arch with coarctation and clinically nonsignificant disease in the infrarenal aorta. Division of the nondominant aortic arch was done through a left thoracotomy, along with resection of the coarctation segment and placement of an interposition Dacron tube graft.
Keywords: double aortic arch; coarctation; aorta